Peran Kebijakan Moneter Dalam Perekonomian : Suatu Kajian Literatur - Edi Irawan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This article aims to review and attempt to inform the concept of the role of monetary policy in the economy. The research method used is qualitative and literature studies or library research. Based on the results of the discussion above, it can be concluded in general that the role of monetary policy in the economy is to keep economic conditions growing and conductive, to create sufficient money supply so that growth can always be in harmony with the course of development which requires strong discipline among monetary authorities and also on the government side and overseeing the development of foreign currency receipts and supervising activities in the foreign sector ( exports and imports). Activities in this sector are very easy to cause inflation in the country, because the price of law materials always fluctuates. Thus, revenues from export activities always experience irregular changes.